Clinical Complications in Outpatient Myelodysplastic Syndromes. (February 2015) - Tendas, Andrea; Niscola, Pasquale; Cupelli, Luca; Scaramucci, Laura; Giovannini, Marco; Piccioni, Daniela; Dentamaro, Teresa; Perrotti, Alessio Pio; de Fabritiis, Paolo
The aim of our research is to evaluate the rate, the type, the severity, the causative factors, and the pathogenesis of complications during the course of myelodysplastic syndromes (MDS). Complications among MDS patients on outpatient management were prospectively recorded and classified. During an 18-month observation period, complications emerging in 48 outpatients with MDS, of whom 15 (31%) were on active treatment and 33 (69%) were receiving best supportive care alone, were recorded and analyzed. Out of 48 patients (median age, 72 years), 34 (71%) experienced complications; a total number of 92 events were recorded; most frequently observed events were infections (43 events, 47%) and bleeding (11 events, 12%). Complications are a frequent issue in MDS; preventive measures should be directed toward the most frequently observed complications.